The Impact of Legislative Environment on the Development of Islamic Banking: A Comparative Study between Malaysia and Afghanistan - Naseh, Hezbullah; Ghalia, Bouhedda (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
This article examines the impact of the legislative environment on the development of Islamic banking through a comparative analysis study of Malaysia and Afghanistan context. The problem statement highlights how differing legal frameworks in both countries affect the growth and effectiveness of Islamic banking systems. The research objective is to assess how Malaysia's well-established legal environment has facilitated the development of Islamic banking, compared to Afghanistan's evolving legal landscape.. The study employs an analytical and comparative approach to examine key legislative and regulatory differences, focusing on factors such as market penetration, operational efficiency, and Shariah compliance. The findings reveal that a supportive legal and regulatory structure is essential for the success of Islamic banking, suggesting that Afghanistan could improve its legislative framework by adopting best practices from Malaysia's experience.